Hanging Position of Artificial Nest Boxes Affects Reproductive Success of Russet Sparrow Passer cinnamomeus - Pan Peng; Wanzhu Chen; Nursoltan Qianhan; Hang Yu; Qian Hu; Jiagui Zhu; Hua Huang; Zhiyong Du; Jianqiang Li (Animals)
Secondary cavity-nesting birds can utilize artificial nest boxes provided by humans for breeding, making nest boxes important approaches for attracting birds. Artificial nest boxes are therefore widely used in fields such as ornithological research and avian diversity conservation. Under natural conditions, the location of nests often affects the reproductive success of birds. Therefore, understanding the impact of nest box hanging positions on the breeding success of secondary cavity-nesting birds is of great significance for guiding the placement of artificial nest boxes. In this study, we explored the potential factors, including nest-box location, that affect the reproductive success of the russet sparrow (Passer cinnamomeus) by monitoring the nest-site characteristics and reproductive parameters such as clutch size and brood size of those breeding in artificial nest boxes near Dongzhai National Nature Reserve, Henan, China, from April to July 2024. Russet sparrow nesting in boxes on coniferous trees and utility poles showed no significant differences in clutch size, hatching rate, brood size, pre-laying nest-abandonment rate, and whether the breeding was ultimately successful. Nests with earlier egg-laying dates had larger clutch sizes, higher hatching rates, and greater brood sizes. However, the number of fledglings and fledging success were not affected by laying date, and fledging success was not affected by either the distance from the nest site to the nearest road, or the brood size. Both larger brood size and greater distance from the nearest road were associated with increased numbers of fledglings. Furthermore, russet sparrows nesting in boxes on coniferous trees produced significantly more fledglings and exhibited higher fledging success compared to those nesting on utility poles, suggesting that nest boxes’ hanging position may influence russet sparrow reproductive success. These findings not only supplement existing ecological data on russet sparrow reproduction in artificial nest boxes but also provide important insights for avian conservation practices, highlighting the necessity of fully considering hanging position when deploying artificial nest boxes for birds.